A Social Network Perspective on Relationship Management in the Human Resource Outsourcing Network: Examining the Moderating Impact of HR Task Interdependence. Issue 4 (26th July 2013) - Yan, Ming; Marie Francesco, Anne; Zhang, Haina; Chen, Yang; Kaše, Robert; King, Zella; Minbaeva, Dana
Abstract Recognizing that managing the outsourcing relationship is critical to the success of a human resource outsourcing (HRO) strategy, we draw on two theoretical perspectives in social network research, integrating open‐ and closed‐triad network structures, to develop a balanced HRO network framework through the moderating impact of HR interdependence. We use this framework to identify the relationships among the HR department that outsources certain HR functions, the groups of internal employees served by the HRO programs, and HR service vendors providing these outsourced HR services. We also consider strategies on how to manage HRO relationship structure to achieve competitive advantage in HR practice. The present study is an attempt to advance the HRO literature from a focus on a "make or buy" decision to a broader model of HRO relationship management.